Analisis Pengendalian Biaya Produksi Melalui Beban Pokok Penjualan Dan Margin Laba Kotor di PT Japfa Comfeed Tbk Tahun 2024 - Rumia Marito Siregar; Listra Debora Siahaan; Juniati Debora; Ferry Fernando Wicaksana Siagian; Hamonangan Siallagan (Lembaga Pengembangan Kinerja Dosen, 2025)
Controlling production costs is essential for the efficiency and sustainability of the company. This study analyzes PT Japfa Comfeed Indonesia Tbk's production cost control in 2024 through cost of goods sold (COGS) and gross profit margin. Using a qualitative descriptive method with literature study, this study compares 2024 data with 2023. The results showed that raw material costs fell 0.33%, but direct labor costs rose 11.14% and factory overhead costs rose 9.11%. As a result, total production costs rose by 1.45%. The 2.10% increase in COGS was considered reasonable as net sales also increased by 9%. Significantly, the company's gross profit margin increased from 14.7% in 2023 to 20.1% in 2024. This indicates the success of PT Japfa Comfeed Indonesia Tbk in its production cost control strategy. Nonetheless, close monitoring of rising direct labor and factory overhead costs is required to maintain efficiency in the future.